Analisis Faktor Fisik Lingkungan Terhadap Indeks Populasi Lalat di Pasar Baru Kabupaten Ogan Komering Ulu - Yansyah, Eka Joni; Sari, Putri Mayang (Poltekkes Kemenkes Denpasar, 2024)
The higher the number or density of flies, it can indicate that environmental sanitation in that place is not bad and can indicate that human behavior around the place is not clean. The purpose of this study was to analyze the waste management system and physical environmental factors on the fly population index in Pasar Baru, Baturaja Timur District, OKU Regency in 2024. The research method used was the cross-sectional method. The research sample consisted of 60 respondents. The samples to be used in this study were 60 traders and 60 fly measurement locations. The univariate analysis in this study was the fly population index, room temperature, and air humidity in Pasar Baru, Baturaja Timur District. The bivariate analysis used the Chi Square test with a confidence level of 95%. The results of the study showed no significant relationship between room temperature and the fly population index in Pasar Baru, Baturaja Timur District, OKU Regency in 2024 with a P Value of 0.235 and no significant relationship between air humidity and the fly population index in Pasar Baru, Baturaja Timur District, OKU Regency in 2024 with a P Value of 0.134. Traders are expected to independently provide trash bins in accordance with regulations, separate trash bins for dry and wet waste, waterproof and closed.